The associated network embedded decision-making authority allocation and risk-taking of enterprise groups - Ning Wang; Fengjuan Wang (PLoS ONE, 2025)
This research examines the impact of the internal allocation of decision-making authority on the risk-taking behavior of enterprise groups, based on a sample of A-share listed parent-subsidiary companies from 2010 to 2022. The study finds that a centralized decision-making structure is associated with reduction in the overall risk profile of enterprise groups. This paper further employs a mechanism analysis through the establishment of a moderated mediation model with an associated network, which reveals that the centralization of internal decision-making authority achieves a reduction in the level of risk-taking through the operation of the internal capital market through two distinct mechanisms. Firstly, it operates the internal capital market, which suppresses diversified investments. Secondly, it improves the efficiency of internal capital allocation. Furthermore, when the associated network is embedded in the internal capital market model, the moderating effect demonstrates that the internal interlocking director network does not suppress diversified investments, but significantly enhances the efficiency of the internal capital market. The associated network of institutional investors serves to reinforce the risk-reducing effect of the internal capital market on risk by reducing noise trading and signal transmission through the diversification and efficiency enhancement of the internal capital market. This paper illuminates the characteristics of network relationships within the internal capital market and the impact of decision-making authority allocation on enterprise risk, and provides strategies to prevent and mitigate significant economic and financial risk.